Rapid Diagnostics for Hepatitis B and C Viruses in Low- and Middle-Income Countries - Shenge, Juliet A.; Osiowy, Carla (Frontiers in Virology, 2021)
The global health challenge posed by hepatitis B virus (HBV) and hepatitis C virus (HCV) persists, especially in low-and-middle-income countries (LMICs), where underdiagnosis of these viral infections remains a barrier to the elimination target of 2030. HBV and HCV infections are responsible for most liver-related mortality worldwide. Infected individuals are often unaware of their condition and as a result, continue to transmit these viruses. Although conventional diagnostic tests exist, in LMIC they are largely inaccessible due to high costs or a lack of trained personnel, resulting in poor linkage to care and increased infections. Timely and accurate diagnosis is needed to achieve elimination of hepatitis B and C by the year 2030 as set out by the World Health Organization Global Health Sector Strategy. In this review rapid diagnostic tests allowing for quick and cost-effective screening and diagnosis of HBV and HCV, are discussed, as are their features, including suitability, reliability and applicability in LMIC, particularly those within Africa.